Comparative Study of Environmental Education in Adolescents and Higher Education Students - Shair, Bilques; Akhtar, Rukhsana (JOURNAL OF INDIAN EDUCATION, 2012)
The present study is aimed at examining levels of environmental awareness and implementation of environmental knowledge amongst cross section of students in Jammu and Kashmir. The study is designed to compare the extent of awareness amongst adolescent and higher education students. It was found that overall awareness and implementation of environmental knowledge in adolescents is far below the expectations. Students with higher education were found to have largely satisfactory knowledge and skills for solving environment problems.